Phase Ib open-label, multicenter study of pixatimod, an activator of TLR9, in combination with nivolumab in subjects with microsatellite-stable metastatic colorectal cancer, metastatic pancreatic ductal adenocarcinoma and other solid tumors - Lemech, Charlotte; Dredge, Keith; Bampton, Darryn; Hammond, Edward; Clouston, Andrew; Waterhouse, Nigel J; Stanley, Amanda C; Leveque-El Mouttie, Lucie; Chojnowski, Grace M; Haydon, Andrew; Pavlakis, Nick; Burge, Matthew; et al. (Journal for immunotherapy of cancer, 2023)
BackgroundPixatimod is a unique activator of the Toll-like Receptor 9 pathway. This phase I trial evaluated safety, efficacy and pharmacodynamics of pixatimod and PD-1 inhibitor nivolumab in immunologically cold cancers.Methods3+3 dose escalation with microsatellite stable metastatic colorectal cancer (MSS mCRC) and metastatic pancreatic ductal adenocarcinoma (mPDAC) expansion cohorts. Participants received pixatimod once weekly as a 1-hour intravenous infusion plus nivolumab every 2 weeks. Objectives included assessment of safety, antitumor activity, pharmacodynamics, and pharmacokinetic profile.ResultsFifty-eight participants started treatment. The maximum tolerated dose of pixatimod was 25 mg in combination with 240 mg nivolumab, which was used in the expansion phases of the study. Twenty-one grade 3–5 treatment-related adverse events were reported in 12 participants (21%); one participant receiving 50 mg pixatimod/nivolumab had a treatment-related grade 5 AE. The grade 3/4 rate in the MSS mCRC cohort (n=33) was 12%. There were no responders in the mPDAC cohort (n=18). In the MSS mCRC cohort, 25 participants were evaluable (initial postbaseline assessment scans >6 weeks); of these, three participants had confirmed partial responses (PR) and eight had stable disease (SD) for at least 9 weeks. Clinical benefit (PR+SD) was associated with lower Pan-Immune-Inflammation Value and plasma IL-6 but increased IP-10 and IP-10/IL-8 ratio. In an MSS mCRC participant with PR as best response, increased infiltration of T cells, dendritic cells, and to a lesser extent NK cells, were evident 5 weeks post-treatment.ConclusionsPixatimod is well tolerated at 25 mg in combination with nivolumab. The efficacy signal and pharmacodynamic changes in MSS mCRC warrants further investigation.Trial registration numberNCT05061017.